NANTEN 12CO (J = 1 → 0) observations around the star WR 55 - Duronea, Nicolás Urbano (2012)
Context. We present a complete study of the molecular and ionized gas in the environs of the nebula RCW 78 around WR 55. Aims. We investigate the spatial distribution, physical characteristics, and kinematical properties of the molecular gas linked to the galactic nebula RCW 78 to obtain a clearer understanding of its interaction with both the star and the ionized gas. Methods. Our study is based on 12CO(1-0) fully sampled observations of a region of ∼0°.45 in size around the star WR 55 and the nebula RCW 78 obtained with the 4-m NANTEN telescope, radio continuum archival data at 1.4 and 4.85 GHz, obtained from the SGPS and PMNRAO Southern Radio Survey, respectively, and available infrared MIPSGAL images at 24 μm. Results. A molecular gas component in the velocity range from ∼-58 km s-1 to-45 km s-1, which is compatible with the velocity of the ionized gas, was found to be associated with the optical nebula. Adopting a distance of ∼5 kpc, the mass of this molecular component is about 3.4 × 104 M⊙ . Our analysis of the molecular data reveals a velocity gradient that is consistent with that found for the Hα line. New radio-continuum flux-density determinations confirm the thermal nature of RCW 78. This indicates that the ionized gas in RCW 78 arises from the photoionization of the molecular gas component in the velocity range from-58 km s-1 to-45 km s-1. A molecular concentration at a velocity of-56.1 km s-1 (identified as C1) is likely associated with the star HD 117797 and with an ensemble of candidate YSOs, lying at a distance of 3.9 kpc, while the rest of the molecular gas at velocities between-56 km s-1 and-46 km s-1 constitute an incomplete ring-like structure expanding around WR 55 at a velocity of about ∼5 km s-1. Mechanical energy and time requirements indicate that WR 55 is very capable of sustaining the expansion of the nebula.